Humus - Kanor, Fabienne (CARAF books., 2020)
"A novel based on a March 23, 1774, report by Louis Mosnier, captain of a slave ship, recounting an incident in which fourteen African women escaped from the ship's hold to leap overboard. Kanor focuses on the fourteen unnamed women, reinvesting them with identities and voices to narrate this harrowing story. Humus provokes lively discussion on the relationship between fear and the abusive exercise of power; the long-term effects of legitimized systems of exploitation in individual lives at all points in the hierarchy"--